Citrullinated inter-alpha-trypsin inhibitor heavy chain 4 in arthritic joints and its potential effect in the neutrophil migration. (20th December 2020) - Osada, A; Matsumoto, I; Mikami, N; Ohyama, A; Kurata, I; Kondo, Y; Tsuboi, H; Ishigami, A; Sano, Y; Arai, T; Ise, N; Sumida, T
Summary: The citrullinated inter-alpha-trypsin inhibitor heavy chain 4 (cit-ITIH4) was identified as its blood level was associated with the arthritis score in peptide glucose-6-phosphate-isomerase-induced arthritis (pGIA) mice and the disease activity in patients with rheumatoid arthritis (RA). This study aimed to clarify its citrullination pathway and function as related to neutrophils. In pGIA-afflicted joints, ITIH4 and cit-ITIH4 levels were examined by immunohistochemistry (IHC), immunoprecipitation (IP) and Western blotting (WB), while peptidylarginine deiminase (PAD) expression was measured by reverse transcription–quantitative polymerase chain reaction (RT–qPCR), IHC and immunofluorescent methods. The pGIA mice received anti-lymphocyte antigen 6 complex locus G6D (Ly6G) antibodies to deplete neutrophils and the expression of cit-ITIH4 was investigated by WB. The amounts of ITIH4 and cit-ITIH4 in synovial fluid (SF) from RA and osteoarthritis (OA) patients were examined by I.P. and W.B. Recombinant ITIH4 and cit-ITIH4 were incubated with sera from healthy volunteers before its chemotactic ability and C5a level were evaluated using Boyden's chamber assay and enzyme-linked immunosorbent assay (ELISA). During peak arthritic phase, ITIH4 and cit-ITIH4 were increased in joints while PAD4 was over-expressed, especially in the infiltrating neutrophils of pGIA mice. Levels of cit-ITIH4 in plasma and joints significantly decreased upon neutrophil depletion. ITIH4 was specifically citrullinated in SF from RA patients compared with OA patients. Native ITIH4 inhibited neutrophilic migration and decreased C5a levels, while cit-ITIH4 increased its migration and C5a levels significantly. Cit-ITIH4 is generated mainly in inflamed joints by neutrophils via PAD4. Citrullination of ITIH4 may change its function to up-regulate neutrophilic migration by activating the complement cascade, exacerbating arthritis. Graphical Abstract: